TCP1 promotes the progression of malignant tumours by stabilizing c-Myc through the AKT/GSK-3β and ERK signalling pathways - Hekun Liu; Linying Chen; Yuwen Chen; Yiyi Jin; Xiance Chen; Nengjun Ma; Fan Yang; Huixia Bi; Xinxin Wen; Shenmin Xu; Juan Chen; Yanping Lin; et al. (Communications Biology)
Abstract The chaperonin tailless complex polypeptide 1 (TCP1) is a key subunit of chaperonin containing TCP1 (CCT) that regulates the folding and stability of proteins during cancer progression. Here, the prognostic significance of TCP1 was explored mainly in patients with hepatocellular carcinoma (HCC) and pancreatic ductal adenocarcinoma (PDAC). We showed that TCP1 expression was significantly greater in clinically malignant tumour tissues than in normal tissues and that high TCP1 expression was associated with poor prognosis. TCP1 suppression not only decreased the proliferation and invasion of cancer cells in vitro but also inhibited tumour growth and metastasis in vivo. The underlying mechanisms were determined by ubiquitination assays and Co-IP (Co-Immunoprecipitation) experiments, and it was found that TCP1 regulated the stability of c-Myc through the RAC-alpha serine/threonine-protein kinase (AKT) /Glycogen synthase kinase 3β (GSK-3β) and extracellular regulated protein kinases (ERK) signalling pathways. Moreover, TCP1 knock-in (TCP1-KI) dramatically promoted the occurrence of diethylnitrosamine (DEN) -induced primary HCC in mice. Our results highlight the critical role of TCP1 in HCC and PDAC and reveal a novel mechanism to suppress HCC and PDAC by targeting c-Myc via the TCP1-induced promotion of the AKT/GSK-3β and ERK signalling pathways. TCP1 is able to modulate the stability of target proteins by multiple pathways, thus promoting the progression of HCC and PDAC. Our study identifies TCP1 as a prognostic novel marker and therapeutic target of HCC and PDAC.